Does Trade Openness Foster Unemployment? Evidence from D-8 OIC Countries - Ulima, Ananda Olga (Universitas Islam Internasional Indonesia, 2022)
This study aims to analyse the effect of trade openness, wages, inflation, economic growth, and population toward unemployment in the D-8 Organization of Islamic Cooperation countries over the period, 1991 to 2020. The quantitative approach uses techniques analysis of panel data regression. The study result shows a significant simultaneous effect of trade openness, wages, inflation, economic growth, and population on unemployment of D-8 OIC member countries. While partially, trade openness has a significant positive effect on unemployment, wages, economic growth, and inflation have a significant negative relationship with unemployment. The population has a significant positive effect on unemployment. Overall, the result implies that each OIC member country should promote an effective and strategic plan to enhance the demand for labour and employment. Furthermore, professional courses and vocational training should be initiated to fulfil the growing demand for skilled labour.